Lacan's Medievalism - Labbie, Erin Felicia (Book collections on Project MUSE., 2006)
One of the foundational premises of Jacques Lacan's psychoanalytical project was that the history of philosophy concealed the history of desire, and one of the goals of his work was to show how desire is central to philosophical thinking. In Lacan's Medievalism, Erin Felicia Labbie demonstrates how Lacan's theory of desire is bound to his reading of medieval texts. She not only alters the relationship between psychoanalysis and medieval studies, but also illuminates the ways that premodern and postmodern epochs and ideologies share a concern with the subject, the unconscious, and language, thu.